PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DEPARTEMEN UMUM PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA KENCANA SAMARINDA - Qusnul Fadhilah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the work environment and work motivation on employee performance at the Regional Public Company for Drinking Water (PERUMDAM) Tirta Kencana, Samarinda City. This research uses a quantitative approach method. The sample used was 50 employees. The data collection method was through questionnaire distribution. Validity, reliability, multiple regression analysis, classical assumption test, correlation coefficient, coefficient of determination, T test hypothesis test, and F test are some of the data analysis approaches tested. Findings show that employee performance is not significantly affected by the work environment in part. Work motivation has a significant effect on employee performance. Simultaneously the work environment and work motivation have a significant effect on employee performance. Thus, researchers recommend to PERUMDAM to provide lighting in several corners of the work space, rearrange the room layout, provide complete work facilities and tools, increase creativity, provide rewards, and provide opportunities for employees to participate in making policies for the company's progress.